(untitled) (Indian Journal of Arid Horticulture, 2025)
Eighteen-year-old plants of guava cv. ’L-49’ were subjected to various treatments comprising organic manures, inorganic fertilizers and PSB i.e., 100, 50 and 25 per cent of recommended dose of NPK, FYM @ 75 kg per plant, vermicompost @ 10 kg per plant, neemcake @ 5 kg per plant, PSB @ 20 g per plant. In this way, total 14 treatments were used in the present study. The results revealed that all the treatments had significantly increased the quality of fruits over absolute control. Further, the application of organic manures was found significantly superior over 100 per cent recommended dose of NPK. Among the different organic manures used in the present study, the application of vermicompost @ 10 kg per plant significantly improved fruit quality in terms of TSS (14.75 %), acidity (0.434%), ascorbic acid (207.4 mg/100 g pulp) and TSS : acid ratio (34.71) as compared to FYM @75 kg per plant and neemcake @ 5 kg per plant treatment. Among the different levels of recommended dose of NPK, the application of 50 per cent recommended dose of NPK treatment also improve the quality of fruits as compared to 25 per cent recommended dose of NPK. Similarly, the application of PSB @20 g per plant was found to be superior with respect to quality of fruits in level of significance.